Novel Agents in the Treatment of Pancreatic Adenocarcinoma - Dimou, Anastasios; Syrigos, Konstantinos N; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
The development of new agents and treatment strategies against pancreatic adenocarcinoma is vital, given the poor prognosis of the patients with this particular type of cancer. Three novel compounds were tested at different phases of clinical research and the results were presented in the recent ASCO Gastrointestinal Cancers Symposium. FG-3019 inhibits the connective tissue growth factor which is important in the biology of pancreatic cancer and was shown to be relatively safe in a phase I study (Abstract #213). In addition, ASG-5ME, an antibody specific for SLC44A4 that is universally expressed in pancreatic cancer and also carries a conjugate chemotherapy particle was safe at the appropriate dosing in a phase I trial (Abstract #176). Last but not least, tanespimycin, a molecule that inhibits heat shock protein 90 was not effective in the first line treatment of patients with pancreatic cancer in a phase II study (Abstract #245). Further studying of FG-3019 and ASG-5ME will show the potential activity if any of these compounds in patients with pancreatic cancer. Image: Albert Einstein Medical Center. Philadelphia, PA, USA.